Barely even friends : a novel - Bennett, Mae (Alcove Press, 2024)
Bellamy Price has just been offered the job of a lifetime: lead contractor on the restoration of the mysterious and sprawling Killington Estate. If she meets the owner’s ridiculous timeline, she’ll finally make a name for herself in this male-dominated industry. But when she rolls up her sleeves, slips on her suspenders, and shows up at the crumbling mansion, Bellamy finds the estate very much occupied. After a traumatic car accident that left his parents dead and himself injured, Oliver Killington, heir to the Killington empire, took up residence as the grumpy caretaker of his grandfather’s mansion. None too pleased by the presence of the hammer-wielding woman who’s moved into his house, Oliver tries to block her at every turn. But when Bellamy discovers Oliver’s facing his own ultimatum from his grandfather, the two form a cautious truce, which leads to flying sparks that are definitely not from faulty wiring. As Bellamy restores the gleam to the Killington Estate, she’ll have to decide if the walls she’s built around herself are worth knocking down to make space for someone else.